A educação integrada e a profissionalização no ensino médio - Dias, Vagno Emygdio Machado (2015)
The objective of this thesis is to analyze the Integrated Education, generic name of Professional and Technical Education in middle level combined with a secondary school in integrated mode, under the Law of Directives and Bases of National Education (LDB 9.394/1996) updated through Decree 5.154/2004. We sought to understand what is the integrated education: definition, characteristics, social and political purposes, theoretical-methodological referential and pedagogic-didactic fundamentals. The methodological proceedings was marked: on one hand, by theoretical analysis of the education and of the socialist pedagogy in the thought of Karl Marx, Vladimir Lenin, Nadezhda Krupskaya, Anatoli Lunacharsky and Antonio Gramsci, specifically on the concepts of technology education, polytechnic education and unitary school. On the other by a theoretical and documentary analysis of the legislation, other official documents and literature on the national education and the recent reforms of education, secondary school and integrated education. The study concluded that in the meanders of the integrated education this underlying a broader process of expanding the spirit of professionalization to practically all the Brazilian education system, especially for secondary school. The reform of secondary school, it happened in parallel and conditioned a professionalizing reform.